Effect of Methyl Jasmonate on In Vitro Callus Growth of Momordica cochinchinensis - Isima, Widyawati S.; Ahmad, Jusna; Pagalla, Devi Bunga; Kandowangko, Novri Youla; Husain, Indriati (Jurnal Biologi Tropis, 2026)
Momordica cochinchinensis (Lour.) Spreng., locally known as dumbaya in Gorontalo, is a tropical climbing plant with potential as a functional food and medicinal resource, but its natural availability is limited by low seed germination, slow growth, and environmental sensitivity. This study aimed to determine the effect of methyl jasmonate (MeJA) concentrations on callus growth of young stem explants of M. cochinchinensis under in vitro conditions. The experiment used a completely randomized design with five treatments: MS without plant growth regulators, MS + 2,4-D + BAP, MS + MeJA 6 mL/L, MS + MeJA 11 mL/L, and MS + MeJA 16 mL/L. The observed parameters were callus formation percentage, callus initiation time, and callus morphology. Quantitative data were analyzed using one-way ANOVA followed by Duncan’s test at 5%, while morphological data were described qualitatively. All treatments produced 100% callus formation within 14 days. MeJA affected callus initiation time, with MS + MeJA 6 mL/L showing the fastest average response at 3.67 days after culture. The callus was mostly friable with varied coloration. This treatment may support further development of M. cochinchinensis callus culture and provides preliminary information for optimizing in vitro propagation protocols for this locally valuable species in future studies.